Food uptakes and enzyme activities when the Siberian sturgeon, Acipenser baeri (Brandt, 1869), feeds continuously or limitedly - Kim , Su-Kyoung; Chul, Ho Lee; Chae, Sung Lee; Young, Dae Kim; Qtae, Jo; Rahman, Mohammad Mustafizur; Rosenthal, Harald (2008)
Total feeding rates and digestion effectiveness of the Siberian sturgeon were determined for a limited one-hour feeding and for continuous feeding. The mean fork length was 13.7 1.7 (S.D) and mean weight was 12.0 3.2 (S.D) g for the individuals used in these experiments. Continuous feeding induced subsequent weight increase of the stomachs but the weight of digestive tracks were relatively constant (Fig. 1). The maximal weight ratio was recorded 8 hours after feeding in the continuous feeding group and 1-2 hours after feeding in the group fed only for an hour. Trypsin activities in digestive tracks showed different peak values depending on the feeding method (Fig. 2). Limited feeding induced more trypsin activity in total digestive track. The highest trypsin activity showed 4 hours post feeding in both feeding groups. However, the level of activity in limited feeding, either mg unit digestive track or total dried weight of digestive track, was higher in the continuous feeding group.